Inflation and the public investment: Growth relationship in Vietnam - Nguyen, Van Bon (University of Economics Ho Chi Minh City, 2023)
Public capital spending positively contributes to economic growth and development in many countries worldwide. However, questions concerning the importance of inflation in the public investment–growth relationship are of great interest. This study examines the role of inflation in the public investment–growth relationship in Vietnam using the two-step GMM Arellano-Bond estimators for a balanced panel data of 52 provinces during the period of 2005–2014. More interesting are the empirical findings. First, inflation significantly increases the volume of public capital spending. Second, public investment and inflation enhance economic growth, but their interaction term impedes it. Third, private investment, government recurrent expenditure, and trade openness are the significant determinants of growth. These findings suggest some important policy implications related to public capital spending and inflation in developing countries, specifically the Vietnam government.